Hospedagem compartilhada: uma análise dos fatores que influenciam sua escolha - Braga, Paulo Roberto de Freitas (2023)
The sharing economy in the accommodation sector is a growing trend driven by a combination of factors involving consumer behavior, leading people to seek more affordable travel options. In this conception, accommodation, generally chosen through digital platforms, such as AirBnb and Couchsurfing, is characterized by sharing spaces, encouraging interaction between guests and between them and the host. In line with this perspective, this study aimed to identify the factors that influence Brazilian consumers (tourists) to opt for shared accommodation. A descriptive research was carried out, with a quantitative approach through a Survey, using an electronic questionnaire, covering eight dimensions: i) Cost savings; ii) Familiarity; ii) Trust; iv) Utility; v) Social and cultural experiences; vi) Quality of service; vii) Satisfaction; and viii) Reuse. Consumers who had already taken at least one national or international trip using shared accommodation were investigated. The results showed that male travelers are more likely to use shared accommodation. It was also possible to identify that the dimensions of trust, usefulness and quality are those that most influenced the choice of shared hosting, also influencing user satisfaction and, consequently, the predisposition of these consumers to reuse shared hosting modalities. This study contributes by revealing that other factors, in addition to economic aspects, influence the choice for shared hosting. This discovery points to the need for adaptation on the part of traditional hosting companies, which must rethink their competitive strategies in response to this new reality.